Pelaksanaan Kelas Ibu Hamil Dengan Kemandirian Ibu Primipara Dalam Perawatan Neonatus Di Puskesmas Sukorame Kota Kediri - Shinta Kristianti; Ari Kusmiwiyati (coba, 2017)
A woman who suffered on first pregnancy, often do not know how to care for the baby later. Parents of babies are considered inadequate in providing care to the baby. Antenatal Class means to learn together about the health of pregnancy, midwives can teach and support the mothers to care of her baby. This research aimed to know the relationship class implementation with primiparas’s autonomy in neonatal care. The design was an analytic correlation with cross sectional approach. The population was 35 primigravidas with gestational age of 29-36 weeks on Puskesmas Sukorame Kediri. Sampling technique used was purposive sampling. The samples were 22 respondents who met the inclusion criteria. Test data analysis using Fisher exact test with a significance of 5%. Based on the results count by probablity fisher exact test for α error level of 5% (0.05) was obtained p (count) 0.054 greater than 0.05. It can be concluded that the p (count) is greater than the specified error level, so H-0 accepted, which means there was no correlation of Antenatal Class Implementation to Primipara’s Autonomy in Neonatus Care. Keywords: Pregnancy Class, autonomy, primigravida, primipara, Neonatus